PERAN ORANG TUA, TEMAN SEBAYA DAN LINGKUNGAN DENGAN KEPATUHAN PROTOKOL KESEHATAN COVID-19 PADA SISWA SMPN 6 KOTA BEKASI TAHUN 2021 - Khalidiyah Hafizhah (2021)
The COVID-19 SATGAS team noted that in march 2021 there were 36.634 positive confirmed cases in children aged 13-15 years (SMP) with 58 cases of death. The increasing number of COVID-19 cases shows that compliance with health protocols has not been implemented properly. The purpose of this study was to determine the relationship between the role of parents, peers, and environment with COVID-19 health protocol compliance in students of SMPN 6 Bekasi City 2021. The quantitative research method with cross-sectional design, using purposive sampling technique. The number of sampels is 265 students. Data analysis using chi-square test. The result of this study show that there is a relationship between the parental role variable and the compliance of the COVID-19 health protocol in students (p= 0.000), the relationship between the peer role variable and the COVID-19 health protocol compliance in students (p = 0.001), the relationship between environmental variables and COVID-19 health protocol compliance in students (p= 0.001). It is hoped that students will be more obedient to the COVID-19 health protocol.